NORMATIVE AND LEGAL BASES OF PUBLIC MANAGEMENT AND ADMINISTRATION OF THE PROCESS OF EDUCATION OF THE POPULATION OF UKRAINE IN THE SPHERE OF CIVIL PROTECTION - Kropyvnytskyi V. S., (Pressing Problems of Public Administration, 2021)
The analysis of the existing normative and legal documents on the issues of educating the population on actions in emergency situations is carried out. The peculiarities of the system of public administration and administration in the sphere of civil protection in modern conditions on the issues of educating the population on actions in emergency situations are described. The problematic aspects and contradictions of the existing legal framework on public education regarding actions in emergency situations are identified. The ways of solving problems and resolving the contradictions of the system of public administration and administration in the sphere of civil protection in modern conditions on the issues of educating the population on how to act in emergency situations are clarified. Analysis of legal sources through which the public management and administration of the process of training the population of Ukraine to act in emergencies shows that this issue is not sufficiently regulated at the legislative level, although existing regulations are constantly updated to meet current requirements. It was found that despite the current legal framework and detailed procedure for educating the population, their awareness of civil protection (including fire safety) is quite low, as evidenced by the number of victims and deaths due to emergencies (fires). This state of affairs is a consequence of: non-compliance of the organization of training with the requirements of regulatory documents; inconsistencies of programs and training procedures with modern challenges and events; due to the lack of competent specialists who should provide such training in the field of civil protection. Therefore, in modern conditions, the construction of an effective and efficient system of public administration and administration of the process of training the population of Ukraine in the field of civil protection, improving the existing legal framework (including amendments to the Civil Protection Code of Ukraine), its adaptation to existing world practices and European legislation within the process of European integration of Ukraine.